Основні засади формування конкуренції підприємств галузі птахівництва - Кравченко, Микола Володимирович; Kravchenko, M. V.; Kravchenko, Mykola; Іжболдіна, Олена Олександрівна; Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; Izhboldina, Е.; Izhboldina, Olena (Одеський нац. ун-т ім. І. І. Мечникова, 2019)
У статті висвітлені теоретичні засади формування конкурентних переваг підприємств галузі птахівництва. Сформовано методичні підходи щодо управління конкурентоспроможності аграрних підприємств. Обґрунтовано організаційно-економічні заходи щодо підвищення конкурентних переваг підприємств птахівничого комплексу. The article deals with theoretical bases of formation of competitive advantages of agricultural enterprises. Methodical approaches to management of competitiveness of agricultural enterprises. Grounded organizational and economic measures to increase competitive advantages of enterprises of agro industrial complex. A competitive poultry enterprise must not only surpass its competitors in terms of efficient use of internal potential, but also have a flexible, adaptive response to external opportunities and threats. Ensuring the competitive development of enterprises is hampered by unsystematic and scattered receipts of funds for the modernization of their production activities, low investment activity, the lack of comprehensive application of innovative technologies, the imperfection of the economic mechanism for managing the production process and inter-branch relations and economic relations with processing enterprises and trade enterprises, and insufficient state support. The process of studying the competitive advantages of poultry enterprises should be based not only on the characteristics and characteristics of the competitiveness category, but also in full compliance with the specifics of the industry. In this case, before the producers, as the subjects of management, the need to address the following tasks: the assessment of not only the actual level of competitiveness, but also the potentially possible level; reflection in the results of the analysis of the factor component of competitiveness; research of competitive advantages at the level of the subject and products; selection of methods and tools for evaluation according to the specificity of the study. The presented analytical review of methods for assessing the competitiveness and individual competitive advantages, along with the limited specific methods, showed the practical value of each of them.
The basic bases for the competition of battle complexes
Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228
Keywords: інтегровані системи; integrated systems; конкурентні переваги; competitive advantages; організаційні засади; organizational principles; конкурентоспроможність; competitiveness; методичні підходи; methodological approaches; пташине підприємство; avian enterprise